A genetic disease under the multiform mask – infantile-onset of Pompe disease - Jadczak, Klaudia; Kadłubiska, Anna; Semeran, Kornel; Bossowski, Artur (Pediatria Polska - Polish Journal of Paediatrics, 2024)
Acid α-glucosidase deficiency – Pompe disease (PD) is a genetic, autosomal recessively inherited disorder leading to impaired glycogen degradation and storage in cells, especially muscles. It occurs with a frequency of 1 : 10,000 – 1 : 40,000 live births. This article presents a currently 14-year-old girl diagnosed with infantile-onset PD. A 15 days old the girl was referred to the hospital due to tachycardia. On examination, reduced muscle tone and hepatomegaly were observed. Electrocardiography showed supraventricular tachycardia. Laboratory tests detected increased hepatic aminotransferase activity. Echocardiography of the heart showed features of hypertrophy of both chambers. The patient was referred to the Children’s Memorial Health Institute in Warsaw. Pompe disease was diagnosed. At 4 months of age, therapy with Myozyme, administered intravenously every other week, was started, and it continues to the present day. Early recognition of PD and initiation of substitution therapy allow its course to be slowed and patients’ lives to be extended.